Co-variation in biomass and environment at the scale of a forest concession in central Africa. (13th July 2017) - Mankou, Géraud Sidoine; Picard, Nicolas; Ngomanda, Alfred; Loumeto, Jean Joël
Abstract: Drivers of forest structure in central African rain forests are largely unknown. Using forest inventory data (3024 0.4-ha plots) in a forest concession of 154 456 ha in north-eastern Gabon covering an altitudinal gradient (from 485 to 1009 m asl), relationships between above-ground plot biomass and environmental variables (soil type, altitude, slope, aspect) and floristic composition (score given by an ordination method) were tested. After controlling for confounding variables, biomass was significantly related to altitude (with a modal response peaking at 346 Mg ha –1 on western slopes at an altitude of 707 m asl) and to aspect (additional 18.3 Mg ha –1 on eastern slopes) but not to floristic composition. Biomass and basal area responded differentially to the environment. Mean wood density was significantly related to soil, altitude and floristic composition, with a predicted minimum of 0.60 g cm –3 at an altitude of 1009 m asl in stands characterized by Scorodophloeus zenkeri and a maximum of 0.69 g cm –3 at an altitude of 458 m asl in monodominant Gilbertiodendron dewevrei stands. Variation in forest structure in the concession was primarily driven by altitude while floristic composition played a role in differentiating the variation in biomass and basal area.